Indirect Taxation in Developing Countries : A General Equilibrium Approach - Bovenberg, Ary (IMF Working Papers; Working Paper ;, 1986)
Indirect taxes are an important element in stabilization tax packages that aim at raising revenue in the short run. This paper evaluates, by using a general equilibrium model, alternative instruments of indirect taxation in middle-income developing countries. It uses data for Thailand as an illustration and examines the effects on revenue, efficiency, equity, and international competitiveness. The paper shows that the interaction between taxes and distortions caused by various policies can be important for revenue and efficiency. It also reveals significant backward shifting and a link between outward-looking supply-side tax policies and trade policies in industrial countries.